Telemedicine and current clinical practice trends in the COVID-19 pandemic. Issue 3 (October 2021) - Wahezi, Sayed E.; Kohan, Lynn R.; Spektor, Boris; Brancolini, Scott; Emerick, Trent; Fronterhouse, Jean M.; Luedi, Markus M.; Colon, Marc A.; Kitei, Paul M.; Anitescu, Magdalena; Goeders, Nicholas E.; Patil, Shilpavedi; et al.
Abstract : Telemedicine is the medical practice of caring for and treating patients remotely. With the spread of the coronavirus disease-2019 (COVID-19) pandemic, telemedicine has become increasingly prevalent. Although telemedicine was already in practice before the 2020 pandemic, the internet, smartphones, computers, and video-conferencing tools have made telemedicine easily accessible and available to almost everyone. However, there are also new challenges that health care providers may not be prepared for, including treating and diagnosing patients without physical contact. Physician adoption also depends upon reimbursement and education to improve the telemedicine visits. We review current trends involving telemedicine, how pandemics such as COVID-19 affect the remote treatment of patients, and key concepts important to healthcare providers who practice telemedicine.